2017
DOI: 10.1515/jmmm-2016-0159
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal elasticity theory for graphene modeling and simulation: prospects and challenges

Abstract: Abstract:This paper presents a literature review of recent research studies on the applications of nonlocal elasticity theory in the modeling and simulation of graphene sheets (GSs). The history, development and excellent properties of GSs are introduced. The details of nonlocal elasticity theory are also presented. A systematic introduction to the application of nonlocal elasticity on linear modeling and nonlinear modeling for single-layer graphene sheets (SLGSs) and multilayered graphene sheets (MLGSs) is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 86 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…From the results and previous discussion, it is found that the microscale effect is not apparent for structures with dimensions in the order of microns, while it can be noticeable in nanoscale dimensions which is consistent with the observations of Wang and Liew [70]. Also, when the stress at the source of a nanoscale heating problem is determined, the non-local behavior is a key factor which cannot be ignored [16,[48][49][50]. According to this new non-local theory, we must define a new classification for all materials in accordance with the elastic non-Fig.…”
Section: The Effect Of Non-local Parametersupporting
confidence: 87%
See 1 more Smart Citation
“…From the results and previous discussion, it is found that the microscale effect is not apparent for structures with dimensions in the order of microns, while it can be noticeable in nanoscale dimensions which is consistent with the observations of Wang and Liew [70]. Also, when the stress at the source of a nanoscale heating problem is determined, the non-local behavior is a key factor which cannot be ignored [16,[48][49][50]. According to this new non-local theory, we must define a new classification for all materials in accordance with the elastic non-Fig.…”
Section: The Effect Of Non-local Parametersupporting
confidence: 87%
“…The non-local continuum theory expressed by Koutsoumaris et al [48], either in integral or differential forms, is commonly utilized for describing the size dependency in micro-and nanoscale structures. Liew et al [49] literary studied the recent works related to the application of non-local elasticity theory for modeling and simulation of graphene sheets. Rajneesh et al [50] conducted a temporary study on the phase-lagged non-local thermoelastic thick micro-stretches.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (16) indicates that the local amplitude can be corrected for the nonlocal residual with the incorporation of ( ) as a nonlocal residual-based fictitious force. By introducing = / as a nonlocal residual-based correction factor, equation ( 16) can be rewritten in the form:…”
Section: Static Bending Of Nonlocal Euler-bernoulli Beamsmentioning
confidence: 99%
“…integral nonlocal theory, was used to investigate the dispersions of plane waves [9], stress concentrations near a crack tip [4], plasticity and damage of materials [10], softening plasticity [11], mechanics of nonlocal bars [12], and mechanics of nonlocal beams [13]. As for the differential nonlocal theory which depends on a differential operator, an uncountable list of studies were conducted; examples include [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…That graphene could be modeled in the framework of the non-local elasticity has been conjectured in the literature several times. A review of recent research studies on this matter can be found in [20]. Unlike classical continuum models, within the framework of non-local elasticity it is assumed that the stress at a reference point in a body depends not only on the strains at that point, but also on strains at all other points of the body.…”
Section: Introductionmentioning
confidence: 99%